Investigating the psychological and social influences on leadership formation in educational settings - Yukun Li; Ampapan Tuntinakhongul (Environment and Social Psychology, 2025)
This study employs qualitative research methods to explore the factors influencing the development of student leadership among university students. Through the use of open-ended questionnaires and semi-structured interviews, we obtained in-depth insights into participants’ experiences and perspectives. This qualitative approach facilitates a comprehensive examination of key influences, including emotional intelligence, family support, educational environments, and hands-on leadership experiences. Thematic analysis identified four major themes: pathways to acquiring leadership experience, essential leadership competencies, external influences on leadership development, and areas for improvement in leadership training programs. The findings highlight the complex and multifaceted nature of leadership growth, emphasizing the critical roles of emotional intelligence and practical opportunities in cultivating effective leadership among students. This research offers valuable insights to inform leadership development initiatives in higher education contexts.
Keywords: Emotional Intelligence and Performance